Didaskalije in njihova uresničitev v gledališki uprizoritvi Cankarjevih Hlapcev - Žavbi Milojević, Nina (Jezik in slovstvo, 2017)
The paper deals with stage speech realisation of didascalies in theatre production, focusing on the example of stagings of Cankar's Hlapci (Eng.: The Bondsmen, The Servants or The Serfs) directed by Sebastijan Horvat (Slovenian Permanent Theatre in Trieste, 2015). Didascalies are a side text of a drama that is transformed to nonverbal (visible and audible) signs in staging. In the paper, didascalies connected to stage speech are studied, especially their impact on the individual actor's stage speech interpretation and on the stage speech concept as a whole. The research concludes that didascalies are taken into account when they comply with the directorial concept of staging and with the individual actor%s interpretation.
Keywords: "Hlapci"; Cankar, Ivan, 1876-1918; didaskalije; govorna uresničitev; odrski govor; Slovene literature; slovenska dramatika; slovenska književnost; uprizoritve